Effect of Discovery Learning with Science Literacy Toward Students Sains Learning Competences at VII Grade - tut anggraini; Syamsurizal Syamsurizal; Dezi Handayani; Siska Alicia Farma (Bioeducation Journal, 2019)
Student's learning competency which mostly still under Minimum Criterion. This is caused by lack of preparation of student in face of learning process and also more dominated by teacher centered), so the less effective learning process. These problems can be solved by applying discovery learning models containing literacy science. This research is an experimental research with randomized control group design posttest only design. The population of this study is all of the class VII registered in the academic year 2017/2018. The sample was taken by purposive sampling technique that is class VII1 as control class and class VII3 as experiment class. The research instrument used is posttest for knowledge competence and affective and psychomotor observation sheet to see students' affective and psychomotor competence. Hypothesis in this study was tested using t test. The result of the research, concluded that the application of discovery learning model of science literacy can improve the learning competence of science (cognitive, affective and psychomotor) students of class VII.